2021
DOI: 10.14569/ijacsa.2021.0121160
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Domain Knowledge and Time Series Features for Automated Detection of Schizophrenia from EEG Signals

Abstract: Over the recent years, Schizophrenia has become a serious mental disorder that is affecting almost 21 million people globally. There are different symptoms to recognize schizophrenia from healthy people. It can affect the thinking pattern of the brain. Delusions, hallucinations, and disorganized speech are the common symptoms of Schizophrenia. In this study, we have used electroencephalography (EEG) signals to analyze and diagnose Schizophrenia using machine learning algorithms and found that temporal features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Previous EEG mapping studies have found increased beta power and decreased alpha and delta/theta power in deaddictive alcoholic patients, compared to normal controls. Since slow activity is considered inhibitory, fast beta activity excitatory and alpha activity an expression of normal brain function, the desynchronised low-voltage fast patterns can be translated as CNS hyperexcitation [30], [31].…”
Section: A Eeg and Substance Addiction 1) Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous EEG mapping studies have found increased beta power and decreased alpha and delta/theta power in deaddictive alcoholic patients, compared to normal controls. Since slow activity is considered inhibitory, fast beta activity excitatory and alpha activity an expression of normal brain function, the desynchronised low-voltage fast patterns can be translated as CNS hyperexcitation [30], [31].…”
Section: A Eeg and Substance Addiction 1) Alcoholmentioning
confidence: 99%
“…Opinions as to the cause of these EEG changes in alcoholics show that incoherencies in brain function, particularly in frontal parts of the brain, may be participating in the development of alcoholism [5], [30], [31]. This is documented by a variety of studies: beta activity has been linked to the combination of the two pre-morbid factors of childhood behaviour disorders and paternal alcoholism.…”
Section: A Eeg and Substance Addiction 1) Alcoholmentioning
confidence: 99%